Volatile profile of Croatian lime tree (Tilia sp.), fir honeydew (Abies alba) and sage (Salvia officinalis) honey - Lušić, Dražen (Array, 2007)
Volatile profiles of lime tree (Tilia sp.), fir honeydew (Abies alba) and sage (Salvia officinalis) honey produced in Croatia have been studied by using headspace solid phase microextraction (HS-SPME) followed by gas chromatography-mass spectrometry (GC-MS) analysis. Melissopalynological and sensory characterization have been performed in order to check the reliability of botanical origin of the samples. In case of sage honey, sensory characteristics are reported for the first time and are rather uniform including: colour characterized as beige to jade, depending on the consistency; odour characterized as between light and medium intensity, slightly pungent and wooden; taste characterized as low sweetness, expressive acidity and apple caramel, with persistent fruity aftertaste. Characteristic volatile profiles of the analyzed honeys are described. Taking into consideration similarities with lime and fir honey volatile profiles reported in literature, characteristic volatile compounds resulting from qualitative data evaluation are proposed. Sage honey volatile profile has been reported for the first time and it was found quite different compared to the other studied honeys showing the lowest number of peaks among the studied honeys, 34. Several compounds belonging to the sage honey volatile profile have been identifiedfot the first time in honeys